A influência das prateleiras de luz no aproveitamento da luz natural sob obstrução externa (2015)
The research considers the hypothesis that the use of the device known as “light shelf” could contribute to optimize internal natural light distribution and control, improving visual comfort and increasing the building´s energy efficiency. The purpose of the inquiry was to evaluate the device’s influence combined with different types of glasses in condition of external obstruction, resembling the reality of the urbanization model with skyscrapers. Three Brazilian cities in different latitudes were chosen, where a simulation of an office building with windows having different obstruction percentages of the celestial sphere took place. With the help of Daysim software, we analyzed the Useful Daylight Illuminances –UDI, verifying that the increase of vertical buildings in urban centers –the usual model in Brazilian cities- could interfere in the quality of light of the internal atmosphere.